Energy-Aware Server Provisioning and Load Dispatching For Connection-Intensive Internet Services - Chen, Gong; He, Wenbo; Liu, Jie; Nath, Suman; Rigas, Leonidas; Xiao, Lin; Zhao, Feng (NSDI'08: Proceedings of the 5th USENIX Symposium on Networked Systems Design and Implementation, 2008)
Energy consumption in hosting Internet services is becoming a pressing issue as these services scale up. Dynamic server provisioning techniques are effective in turning off unnecessary servers to save energy. Such techniques, mostly studied for request-response services, face challenges in the context of connection servers that host a large number of long-lived TCP connections. In this paper, we characterize unique properties, performance, and power models of connection servers, based on a real data trace collected from the deployed Windows Live Messenger. Using the models, we design server provisioning and load dispatching algorithms and study subtle interactions between them. We show that our algorithms can save a signiﬁcant amount of energy without sacriﬁcing user experiences.